Correlation with viruses enhances network complexity and stability of co-occurrence prokaryotes across the oceans - Bo Wang; Yantao Liang; Kaiyue Lian; Chuyu Zhang; Meiaoxue Han; Min Wang; Hongbing Shao; Andrew McMinn; Hualong Wang (mSystems)
ABSTRACT Viruses play critical roles in shaping microbial distribution, organization, and ecological functions. However, the mechanisms behind the association and structuring of microbiomes with viruses still remain largely unknown. To understand how viruses affect the assembly of marine microbiomes, the network complexity and stability of prokaryotic microbiomes with/without viruses were analyzed and compared using the Tara Ocean Project data set, including samples collected from the Indian Ocean (IO), South Pacific Ocean (SPO), North Pacific Ocean (NPO), Mediterranean Sea, and South Atlantic Ocean. The network complexity of prokaryotic communities was substantially different across oceans, being high in the IO and low in the SPO and NPO. Network complexity and stability of marine prokaryotic microbial communities were enhanced by the influence of viruses: microbiomes associated with viruses were more complex, had a high modularity, and were robust with low fragmentation and vulnerability and higher compositional stability than prokaryotic microbiomes without an association with viruses. Results presented here shed light on how the associations with viruses influenced microbial assembly and their co-occurrence pattern and stability across the oceans. Overall, given such changed environmental characteristics across the oceans, stable and resilient microbiome networks imply that biotic associations with viruses play a critical role in maintaining the integrity and resilience of marine microbiomes and their ecological functions.IMPORTANCEThis study represents the first detailed research on the effects of viruses on the organization of marine prokaryotic microbiomes at the global scale. Biotic factors and environmental heterogeneity directly and indirectly affect microbiome and viral co-occurrence with varied strength. Network complexity and stability of marine microbial communities were enhanced by the influence of viruses. Thus, given such dynamic environmental gradients in the ocean, stable and persistent microbiome networks suggest that biotic associations with viruses play a critical role in maintaining the integrity and resilience of marine microbiomes and influencing the function of marine ecosystems.